Contribution of individual phospholipase A2 enzymes to the cleavage of oxidized phospholipids in human blood plasma - Philipp Jokesch; Olga Oskolkova; Maria Fedorova; Bernd Gesslbauer; Valery Bochkov (Journal of Lipid Research)
Phospholipids containing oxidized esterified PUFA residues (OxPLs) are increasingly recognized for multiple biological activities and causative involvement in disease pathogenesis. Pharmacokinetics of these compounds in blood plasma is essentially not studied. Human plasma contains both genuine phospholipases A2 [platelet activating factor acetyl hydrolase (PAF-AH) (also called Lp-PLA2) and secretory phospholipase A2] and multifunctional enzymes capable of removing sn-2 residues in native and oxidized PLs (lecithin-cholesterol acyltransferase, peroxiredoxin-6). The goal of this study was to compare relative activities of different PLA2 enzymes by analyzing cleavage of oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-phosphatidylcholine (OxPAPC) and oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-phosphatidylethanolamine (OxPAPE) by diluted plasma in the presence of enzyme inhibitors. We have found that human plasma demonstrated high total PLA2 activity against oxidized PCs and PEs. PAF-AH/Lp-PLA2 played a dominant role in LysoPC and LysoPE production as compared to other enzymes. Molecular species of oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-phosphatidylcholine and oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-phosphatidylethanolamine could be divided into three groups according to their degradation rate and sensitivity to PAF-AH/Lp-PLA2 inhibitor darapladib. Oxidatively truncated species were most rapidly metabolized in the presence of plasma; this process was strongly inhibited by darapladib. The rate of degradation of full-length OxPLs depended on the degree of oxygenation. Species containing 1 to 3 oxygen atoms were relatively stable to degradation in plasma, while OxPLs containing > 3 extra oxygens were degraded but at significantly slower rate than truncated species. In contrast to truncated species, degradation of full-length OxPLs with > 3 extra oxygens were only minimally inhibited by darapladib. These data provide further insights into the mechanisms regulating circulating levels of OxPLs and lipid mediators generated by PLA2 cleavage of OxPLs, namely oxylipins and LysoPC.